Outcome of Anastomotic Urethroplasty for Bulbar Urethral Stricture Our Experience (Bangladesh Journal of Urology, 2020)
Objective: For evaluation of patients who underwent bulbar end-to-end anastomosis to assess surgical outcome.Materials and Methods: We reviewed 53 patients with an average age of 44 years who underwent bulbar end-to-end anastomosis from January 2013 to July 2018. A total of 9 patients (16.98%) underwent urethrotomy, dilation, or multiple treatments before referral to our center. Stricture length d”2cm, free from infection and completed at least 6 months of follow up were included. Patients were evaluated post operatively by uroflowmetry at 3, 6, 12 months of follow up and yearly thereafter. Clinical outcome was considered a treatment failure when any postoperative instrumentation was needed.Results: Mean age 44 (SD±7.6, range 33 to 54 years). Stricture etiology was blunt perineal trauma 32 (60.37%), infection 12(22.64%), idiopathic 06(11.32%) and iatrogenic 03(05.67%). Mean operation time was 95 minutes (range, 50 to 140 minutes) and mean excised stricture length was 1.4 cm (range, 0.5 to 2 cm). 44 patients (83.02%) were symptom-free and required no further procedure. Strictures recurred in 9 patients (16.98%) within 2 to 5 months after surgery. Of 9 recurrences, 3 patient was managed successfully by urethrotomy, whereas the remaining 6 did not respond to urethrotomy or dilation and required additional urethroplasty.Conclusions: Excision and end-to-end anastomosis urethroplasty is an excellent procedure for short segment bulbar urethral stricture.Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.56-61